DRUG ADDICTION: PERCEIVED STRESS AND SUICIDAL RISK FACTORS - Tariq Rashid; Sana Mustafa; Zainab Asif (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVE: The aim of present study is to investigate and explore the relationship between Perceived Stress and suicidal ideation of drug adcits MATERIAL AND METHOD: Sample of the study consisted of n=100 male addicts, aged 12-50 drawn from Department of Psychiatry and Behavioral Science, Madinah Teaching Hospital, Faisalabad. STUDY DESIGN: Co- sectional study design. PLACE AND DURATION OF STUDY: The sample was taken from MTH of Faisalabad. The duration of study was from 01-6-2015 to 31-10-2015. Inclusion and Exclusion criteria were followed to gather data for this study. Female drug addicts were excluding because female drug addicts were very rare in our society. Perceived stress scale and Suicide Probability Scale (SPS) were used for quantities analysis in the study. After getting data, result was tabulated and analyzed using SPSS version 20. The study result that is based on small sample can be generalized on large population which can build positive approach in people toward their future life RESULTS: In this study descriptive statistical tools were used to analyze the data. Results showed that Suicide probability scale and Perceived stress scale has significantly associated. CONCLUSION: Thus, it can be concluded from the above discussion that is positive relationship between Drug addiction and stress and stress and suicidal rick and stress. It also concludes that age, employment, education, marital status and no of children were strong factors that increase stress and suicidal risk due to addiction.